Correction: Whole-Genome Analysis of the SHORT-ROOT Developmental Pathway in Arabidopsis - Levesque, Mitchell P (Public Library of Science, 2006)

(untitled)
Meta-analysis to combine the results of several microarray experiments reveals a new function for the transcription factor SHORT-ROOT in the development of vascular tissue.